Pengaruh Beban Kerja, Motivasi, dan Kompensasi terhadap Kinerja dan Dampaknya terhadap Loyalitas pada Security di PT Sigap Prima Astrea Kawasan Astra Biz Center - Putri, Vina Tresna; Wahid Akbar Basudani (Lembaga Pengembangan Kinerja Dosen, 2026)
Employee performance and loyalty are fundamental aspects that support organizational effectiveness, especially in the security services industry, where discipline and consistency are highly demanded. This study aims to analyze the influence of workload, motivation, and compensation on employee performance, as well as the mediating role of performance in influencing employee loyalty. The research was conducted on security personnel at PT Sigap Prima Astrea located in the Astra Biz Center. A quantitative approach was applied using a survey method with total sampling involving 48 respondents. Data was collected through structured questionnaires and analyzed using multiple linear regression to test the causal relationships between variables. The findings indicate that compensation has a positive and significant impact on performance, while motivation plays an important role in strengthening loyalty. On the other hand, workload does not have a significant impact on either performance or loyalty, and performance itself does not significantly influence loyalty. These results highlight that well-designed compensation schemes and effective motivation strategies are more impactful in improving performance and building loyalty than workload management. This study contributes to management practices by providing insights for more targeted human resource policy formulation, especially in security service companies. The originality of this research lies in the simultaneous testing of workload, motivation, and compensation with performance as a mediating variable, which is rarely applied in the context of the security services industry.